"Social licence to operate" and the human services: A pathway to smarter commissioning?. Issue 1 (17th July 2018) - Butcher, John R.
Abstract: Externalised service provision is now an embedded feature of Australia's service delivery architecture. However, the lessons drawn from two decades of contracted service delivery suggest that "competition" is an imperfect platform for the delivery of public services, especially where issues of trust in government come into play. Could the concept of a "social license to operate" (SLO), which has been in use in the natural resources sector for over two decades, help to facilitate the conferral of greater trust, credibility and legitimacy upon governments, and externalised service providers in social policy spaces? Abstract : Can the concept of a social licence to operate (SLO) a neglected be applied to the commissioning and procurement of human services? Can the concept be operationalised in the commissioning space in such a way as to facilitate the conferral of greater trust, credibility and legitimacy upon governments and externalised service providers?